Incidence and aetiology of sudden cardiac death in young athletes: an international perspective - Borjesson, M.; Pelliccia, A. (British Journal of Sports Medicine, 2009)
The incidence of sudden cardiac death (SCD) among young athletes is estimated to be 1-3 per 100 000 person years, and may be underestimated. The risk of SCD in athletes is higher than in non-athletes because of several factors associated with sports activity that increase the risk in people with an underlying cardiovascular abnormality. A clear gender difference in the incidence of SCD exists in young athletes, with the risk in male athletes being up to 9 times higher than in female athletes. The most common causes of SCD in young athletes is underlying inherited/congenital cardiac disease, such as cardiomyopathies, congenital coronary anomalies and ion channelopathies. Blunt chest trauma also may cause ventricular fibrillation in a structurally normal heart, known as commotio cordis. Although geographical differences in the causes of SCD in young athletes have been reported, these disparities are more likely to be related to the type and implementation of pre-participation screening leading to the identification of athletes at risk, rather than reflecting a truly different ethiology. More studies are needed to clarify the role of ethnicity in the prevalence of diseases known to cause SCD in young athletes.